INSCRIBED POWER : amulets and magic in early spanish literature. - Giles, Ryan D. (Ryan Dennis) (Toronto Iberic, 2017)
"In Inscribed Power, Ryan D. Giles explores the function of amuletic prayers, divine names, and incantation formulas that were inscribed and printed on parchment, paper and other media, and at the same time inserted into classic literary works in Spain. Giles' insightful analysis of the intersection between amulets and literary texts offers fresh and original interpretations of well-known texts such as the Poema de mío Cid, the Libro de Alexandre, Canitgas de Santa Maria, the Libro de buen amor, Celestina, Lazarillo de Tormes, and the Buscón. Inscribed Power is a fascinating work that highlights specific amuletic texts that were used to heal, protect, or otherwise provide a blessing or curse to discover how their powers could influence fictional lives at different moments in the development of Spanish literature."--